Tumor necrosis factor‐α reduces beta‐amyloid accumulation primarily by lowering cellular prion protein levels in a brain endothelial cell line. Issue 2 (10th December 2014) - Yasutaka, Yuki; Watanabe, Takuya; Nakashima, Akio; Matsumoto, Junichi; Futagami, Koujiro; Yamauchi, Atsushi; Kataoka, Yasufumi
Abstract : Disruption of beta‐amyloid (Aβ) transport across the blood–brain barrier is thought to cause Aβ accumulation in the brain, thus leading to the development of Alzheimer's disease (AD). As AD patients show increased serum tumor necrosis factor‐α (TNFα) levels, we examined the effect of TNFα on the function and expression of Aβ transport‐related proteins including cellular prion protein (PrP C ) in the mouse brain microvascular endothelial cell line MBEC4. TNFα decreased PrP C levels and intracellular radiolabeled Aβ. Similarly, anti‐prion protein antibody also decreased radiolabeled Aβ. These results suggest that TNFα lowers PrP C levels, which in turn, reduces Aβ in the brain endothelium. Abstract : TNFα decreases PrP C levels in brain endothelial cells. TNFα decreases intracellular radiolabelled Aβ levels. Blocking PrP C using an antibody decreases intracellular Aβ levels. TNFα‐lowered PrP C levels decrease endothelial Aβ levels in the brain.